Lived religion in Latin America : an enchanted modernity - Morello, Gustavo (S.I.) 1966- (Oxford University Press, 2021)
This book is about religion and modernity, how religion interacts with modern culture, and how modernity influences religion. By "modernity" I signify not only the technological developments, but also the dynamics of capitalism, the differentiation of social functions and specialization of spheres of knowledge, and the expansion of human rights. In regard to religion, I mean the cultural practices people use to connect with a supra-human power that they experience influencing their lives. The thesis presented is that in Latin America there is an interaction between modernity and religion, but the result has not been religion diminishment (secularization), but its transformation. Exploring religion as ordinary Latin Americans practice it, we discovered that there is more religion than secularists expect, but of a different kind than religious leaders would wish. The difficulty in assessing religiosity as it exists in Latin America is due in part to the continuing use of categories that were not designed for religious cultures outside the North Atlantic world. Those categories point us toward a different kind of dynamics, which in fact obscure Latin American religious dynamics. If we look at religion from Latin America and from the people who practice it, we will find a different definition and different conceptual tools for understanding the religious experience of Latin American people, and perhaps it helps us to look at religion in a different way